Barongsai Form and Color at the Cap Go Meh Festival in Singkawang City - Irsyadi, Muammar; Ekawardhani, Yully Ambarsih (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The aim of this study is to identify the significance of the visual elements of the Barongsai In Singkawang City, West Kalimantan during the Cap Go Meh festival. Qualitative methodologies were used to perform research on the Barongsai visual aspects. Observation, interviews, and documentation are used to acquire data. Due to the predominantly Chinese population, Singkawang City is also known as Amoy City. One of the inherited legacies of art and culture in Singkawang City that is still being preserved today is the Barongsai Dancing Art, which can be seen at the annual Chinese New Year celebrations planned by the Chinese community. According to research, the Barongsai is a mythical animal from Chinese mythology that resembles a lion and comes in two forms: the North Lion and the South Lion. Each form has a distinct meaning based on the visual elements it has. The findings of this study can help comprehend how each Lion Dance performed at the Cap Go Meh festival differs from one another in order to show respect for one of Indonesia’s cultural traditions. This study was conducted in the hopes that it will be useful to researchers who study lion dances in the future. It can be concluded that the visual components of the lion dance are created by paying attention to their beauty as well as considering every meaning that will be associated with them.